Die ‘vyf trane’ as mistieke uitdrukking in die Dialoë van die Dominikaanse non Katharina van Siëna (1347–1380) - Johann Beukes (HTS Teologiese Studies/Theological Studies, 2021)
The ‘five tears’ as mystical expression in the Dialogues of the Dominican nun Catherine of Siena (1347–1380). This article explores the underestimated teaching of the ‘five tears’ as mystical expression in the text Il dialogo (The dialogues, written in 1378) by the Dominican (Mantellate) nun and philosopher-theologian, Catherine of Siena (Caterina Benincasa, 1347–1380). The objective of the article is to indicate the significance of the teaching of the ‘five tears’, against the backdrop of the wider symbolic function of tears and ‘holy grief’ in Late Medieval mysticism. After presenting a biographical introduction, the contemplative, communicative and secretive import of the meaning of tears in the Middle Ages are reappraised and applied to The dialogues. By synthesising the scarce references in the relevant secondary literature, the teaching of the five tears are henceforth discussed: the tears of damnation, which are the tears of ‘evil and sinful people’; the tears of fear, which are the tears of fallen humankind in the presence of God’s judgement; the tears of gratitude, cried by a ‘saved humanity’ who now ‘see and taste God’s goodness’ (implicitly referring to the eucharist); the perfect tears, cried by people in their selfless disposition toward and love for the human Other; and the sweet tears of tenderness, cried by those who love God and humankind, in a radicalisation of Jesus of Nazareth’s summary of the Law, ‘more than thyself’. Catherine’s teaching of the ‘five tears’ certainly presents unique features and its own considerations, but should, nevertheless, be interpreted as an extension of the contemplative and secretive functions of ‘holy grief’ as already presented in Scripture and reconsidered by the Eastern and Western church fathers in the second to the fifth centuries. Catherine’s contribution to Medieval mysticism is established therein that she expanded those initial contents by presenting the teaching of the five tears as a ritualised prerequisite for development in the Medieval pilgrim’s spiritual itinerary to God.